Hubungan Lingkungan Keluarga dan Penggunaan Media Sosial dengan Sikap Toleransi pada Siswa Sekolah Menengah Atas - Rusdiana, Aviana Trisepti; Al Atok, A. Rosyid (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2024)
The purpose of this study is to analyze the relationship between family environment and social media use with students' tolerance attitudes. This study used a quantitative approach with a descriptive correlational type. Family environment and social media use have a significant relationship with students' tolerance attitudes. Family environment with indicators of how parents educate, home atmosphere, and cultural background as a whole produces α 0.05 and α